Perbedaan Patologi Anatomi Tingkat Kerusakan Alveoli Paru dengan Paparan Asap Rokok Konvensional dan Rokok Elektrik - Deka Bagus; Citra Paramita Esti Cahyaningrum (ARTERI : Jurnal Ilmu Kesehatan, 2022)
In conventional cigarettes, tobacco is a major risk factor in the development of diseases involving the lungs, including pulmonary emphysema, fibrosis and lung cancer. Many of people think that using e-cigarettes is much safer than conventional cigarettes. Whereas smoking using electronic cigarettes can cause the same feeling from cotton mouth as felt by conventional smokers with symptoms such as an itchy throat and cough and complications to the lungs. This literature review uses the literature review method by conducting a literature with the keywords cigarette, e-cigarette, popcorn lung and alveoli. The results are in accordance with the objectives of this literature review. The results of the analysis show that there are studies which state that smoking with conventional cigarettes and e-cigarettes can have an impact on damage to alveoli and lung tissue. Conventional cigarettes and electronic cigarettes (e-cigarettes) cause damage to the pulmonary alveoli in the form of alveolar spaces, this depends on the nicotine content in them. Electronic cigarettes and conventional cigarettes exert different effects on the oxidative stress response of the airway epithelium. In addition, the image of popcorn lung can be found due to the presence of diacetyl that appears when heating e-juices in e-cigarettes.